Implementing ISO 9126 in Quality Testing for Information Systems for Menu Ordering Using QR Codes in Panongkrongan Shop - Triyanto, Alvin; Prisilia, Gia; Saputra, Yogi (CV. Generasi Intelektual Digital, 2023)
Panongkrongan Shop is a business that emphasizes the quality of its service. The limited number of employees serving customers has an impact on services that are not optimal, such as ordering errors, delays in ordering menus, price discrepancies because prices are not updated on the menu, transaction errors, and are also prone to loss of order data because the recording is still done manually. A menu ordering system can be built to reduce this problem. However, in its use, the system must be of good quality to support the store's operational activities. The poor quality of the system can cause errors so that those who use it can experience financial losses. For this reason, it is necessary to develop a quality measurement system to run correctly and meet ISO 9126 quality standards. Based on the test results, the system meets ISO 9126 standards with a total score of 91.9% with a functionality aspect of 95.3%, reliability of 83.7%, usability of 93.5%, efficiency of 89.0%, and portability of 98%. Improvements are needed in the reliability aspect, namely in maturity and fault tolerance, so that the system can be even better in terms of quality for error handling and maturity.